Getting Recovery Right After Neck Dissection (GRRAND-F): Mixed-methods feasibility study to design a pragmatic randomised controlled trial - Smith, Toby O.; Garrett, Angela; Liu, Tianshu; Morris, Alana; Gallyer, Victoria; Fordham, Bethany A.; Dutton, Susan J.; Chester-Jones, Mae; Lamb, Sarah E.; Winter, Stuart Charles (Frontiers in Oncology, 2023)
Objective: To determine the feasibility of a randomised controlled trial to estimate the effectiveness and cost-effectiveness of a rehabilitation intervention following neck dissection (ND) after head and neck cancer (HNC). Design: Two-arm, open, pragmatic, parallel, multicentre, randomised controlled feasibility trial. Setting: Two UK NHS hospitals. Participants: People who had HNC in whom a ND was part of their care. We excluded those with a life expectancy of six months or less, pre-existing, long-term neurological disease affecting the shoulder and cognitive impairment. Intervention: Usual care (standard care supplemented with a booklet on postoperative self-management) was received by all participants. The GRRAND intervention programme consisted of usual care plus up to six individual physiotherapy sessions including neck and shoulder range of motion and progressive resistance exercises, advice and education. Between sessions, participants were advised to complete a home exercise programme. Randomisation: 1:1 randomisation. Allocation was based on minimisation, stratified by hospital site and spinal accessory nerve sacrifice. It was not possible to mask treatment received. Main outcome measures: Primary: Participant recruitment, retention and fidelity to the study protocol and interventions from study participants and staff at six months post-randomisation (and 12 months for those reaching that time-point). Secondary: clinical measures of pain, function, physical performance, health-related quality of life, health utilisation and adverse events. Results: 36 participants were recruited and enrolled. The study achieved five of its six feasibility targets. These included consent - 70% of eligible participants were consented; intervention fidelity - 78% participants discharged completed the intervention sessions; contamination - none - no participants in the control arm received the GRRAND-F intervention and retention - 8% of participants were lost to follow-up. The only feasibility target that was not achieved was the recruitment target where only 36 of the planned 50 participants were recruited over 18 months. This was principally due to the COVID-19 pandemic which caused all research activity to be paused or reduced, with a subsequent reduction in. Conclusions: Based on the findings a full-trial can now be designed to better understand whether this proposed intervention is effective.